Microservice architecture : Aligning principles, practices, and culture - Nadareishvili, Irakli (O'Reilly Media, 2016)
"Microservices can have a positive impact on your enterprise--just ask Amazon and Netflix--but you can fall into many traps if you don't approach them in the right way. This practical guide covers the entire microservices landscape, including the principles, technologies, and methodologies of this unique, modular style of system building. You'll learn about the experiences of organizations around the globe that have successfully adopted microservices."--